Les films des géographes français : quelle grille de lecture ? - Luisa Simoes (Unité Mixte de Recherche 8504 Géographie-cités, 2012)
This article aims to provide an overview of films produced by French geographers from the beginning of the 20th century to the present. Starting from the work of Jean Brunhes at the Archives de la Planète and continuing through the pioneering experiments of the 1960s and 70s all the way to contemporary works on digital video, we briefly reconstruct the intellectual and historical contexts that gave rise to these works. We study both the geographical premises and the cinematographic practices that subtend these films. Our aim will be to understand the function these films served within the discipline of geography and to comprehend the ever-increasing use of film by geographers over the course of the last century. Given the varied approaches and variegated functions of these films, we will nonetheless abstain from attempting to regroup these films under the too-rigid category of “the geographic film.” The geographers examined in this study have all had recourse to moving images, yet each has a different conception of the advantages that the audiovisual medium afforded him or her over and against the written text, which remains the standard mode of knowledge production within the discipline of geography.